Autophagy Protects against Sindbis Virus Infection of the Central Nervous System - Orvedahl, Anthony (2010)
Autophagy functions in antiviral immunity. However, it is not yet known whether endogenous autophagy genes protect against viral disease in vertebrates. Using three different approaches to inactivate the autophagy gene Atg5 in virally-infected neurons, we found that loss of Atg5 function increases mouse susceptibility to lethal Sindbis virus CNS infection. This phenotype is associated with delayed clearance of viral proteins, increased accumulation of the cellular p62 adaptor protein, and increased cell death in neurons, but not with altered levels of CNS viral replication. In vitro, p62 interacts with Sindbis virus capsid protein and genetic knockdown of p62 blocks the targeting of viral capsid to autophagosomes. Moreover, p62 or autophagy gene knockdown increases viral capsid accumulation and accelerates virus-induced cell death without affecting virus replication. These results suggest a novel function for autophagy in mammalian antiviral defense: a cell-autonomous mechanism in which p62 adaptor-mediated autophagic viral protein clearance promotes cell survival.